Miniature fiber-optic force sensor for vitreoretinal microsurgery based on low-coherence Fabry-Pérot interferometry - Liu, Xuan (2013)
Vitreoretinal surgery requires delicate manipulation of retinal tissue. However, tool-to-tissue interaction forces in the order of sub-millinewton are usually below the human sensory threshold. A surgical force sensor (FS) compatible with conventional surgical tools may significantly improve the surgery outcome by preventing tissue damage. We have designed and built a miniature FS for vitreoretinal surgery using a fiber-optic common-path phase-sensitive optical coherence tomography (OCT) system where the distal end of the fiber probe forms a low-finesse Fabry–Pérot (FP) cavity between the cleaved tip of the lead-in single mode fiber and the polished back surface of a stainless steel surgical tool tip. To accurately measure the change of the FP cavity length, the cavity is interrogated by the fiber-optic common-path phase-sensitive OCT. The FP cavity was illuminated with a broadband light source, and the interferometric signal was detected using a broadband spectrometer. The phase of the interferometric signal, which is proportional to the cavity length change as well as the exerted force, was extracted. We have conducted calibration experiments to characterize our one dimensional FS. Our result shows that the FS responses linearly to force in axial direction with force sensitivity better than 0.25 millinewton.